Macular morphology after cataract surgery with and without primary posterior continuous curvilinear capsulorhexis - Kang, Chishan; Lin, Kunxia; Huang, Yulong; Yu, Mengting; Wu, Wenjie (Frontiers in Medicine, 2025)
PurposeTo evaluate changes in macular morphology after cataract surgery with and without primary posterior continuous curvilinear capsulorhexis (PPCCC).MethodsA prospective, intraindividual, randomized clinical trial was performed at Fuzhou University Affiliated Provincial Hospital, Fujian, China. A total of 130 eyes of 65 age-related cataract patients with normal macular morphology and function waiting for bilateral cataract surgery and intraocular lens (IOL) implantation were enrolled. Cataract surgery combined with PPCCC was performed in one eye, and routine cataract surgery in the fellow eye (NPCCC group). Optical coherence tomography (OCT) measurements were performed in all patients preoperatively and postoperatively on 1 day, 1 week, 1 month, and 3 months.ResultsA total of 120 eyes of 60 patients were capable to complete scheduled follow-ups and analyzed in the study. There was no statistically significant difference between the PPCCC group and NPCCC group in terms of subfoveal central retinal thickness (CRT), central 1-mm subfield (CSF), average retinal thickness in the middle (1–3 mm) and outer (3–6 mm) rings (p > 0.05) at all timepoints after surgery. Three eyes developed cystoid macular edema (CME) 1-month post-surgery. One eye in the PPCCC group recovered in 2 weeks after topical treatment, while two in the NPCCC group took 8 weeks to recover. In the NPCCC group, PVD progressed in two eyes, one from stage 2 to 4, and another from stage 1 to 2. No PVD progression in the PPCCC group. The corrected distance visual acuity (CDVA) of all patients was logMAR 0.1 or better at the last visit.ConclusionCataract surgery with combined manual PPCCC does not increase the risk of CME and PVD in patients. PPCCC is a safe cataract surgery technique.